Experiential Learning during in-Service Training in Psychopedagogical Centers: A Qualitative Study - Pappas, Nikolaos (Adult Education Critical Issues, 2025)
This particular thesis studies and explores the contribution of experiential learning to acquiring new knowledge and skills in the application of empirical and experiential techniques in- service training programs. The researcher, using a qualitative approach, interviewed a sample of twenty (20) employees in the Psychopedagogical Centers, in order to identify and analyze their views and perceptions on experiential learning and then to investigate the change of knowledge and views which confer efficiency to their work. The research highlights the high degree of acceptance, but also the application of experiential forms of learning, mainly through activities and participatory forms of action within the activities implemented in the workplace. The active participation of the respondents in programs that utilize experiential techniques is recorded as well as the reflection on the changes that take place in the level of their opinions, perceptions and abilities in the workplace.